Cartilage Remodeling in Nasal Tip Rhinoplasty Using "Lateral Crural Steal" and "Tongue in Groove" Strategies: A Randomized Controlled Trial. Issue 4 (14th June 2022) - Gentile, Pietro; Cervelli, Valerio
Abstract : Background: The authors present their experience using "Lateral Crural Steal" (LCS) and "Tongue in Groove" (TING) techniques in nasal tip remodeling. Objectives: The paper aimed to evaluate the efficacy and safety of the use of LCS and TING in nasal tip remodeling for aesthetic improvement. Methods: A randomized controlled trial was conducted. Thirty-five patients affected by low and boxy nasal tips were treated with LCS and TINGs (study group [SG]), comparing results with the control group (CG) (n = 30) treated with cartilage grafts. The preoperative analysis has been performed with an accurate clinical evaluation, a photographic assessment, and a computed tomography scan. Postoperative follow-up took place at 1, 2, and 4 weeks, 3, 6, and 12 months, and then annually. Results: A total of 82.9% (n = 29) of SG patients showed excellent cosmetic and functional results after 1 year compared with the CG patients, who showed the same results in only 40% (n = 12) of cases. The tip projection maintenance and contour restoring in the SG were higher than that in the CG ( P  < 0.0001 versus CG). Conclusions: The use of LCS and TING was safe and effective in this series of cases performed.